Impact of wildfire smoke on Arctic cirrus formation – Part 2: Simulation of MOSAiC 2019–2020 cases - A. Ansmann; C. Jimenez; D. A. Knopf; J. Roschke; J. Bühl; J. Bühl; K. Ohneiser; R. Engelmann (Atmospheric Chemistry and Physics)
A simulation study of the potential impact of wildfire smoke on Arctic cirrus formation is presented. The simulations complement the MOSAiC (Multidisciplinary drifting Observatory for the Study of Arctic Climate) field observations, discussed in Part 1 (Ansmann et al., 2025) of this work. The observations suggest that Siberian wildfire smoke had a strong impact on Arctic cirrus formation in the winter of 2019–2020. Via simulations, a detailed insight into the potential of wildfire smoke to influence Arctic cirrus formation as a function of observed meteorological and environmental conditions (temperature, relative humidity, large-scale and gravity-wave-induced lofting conditions, and ice-nucleating particle (INP) concentration) is provided. Lidar-derived values of the INP concentration serve as input, and ice crystal number concentration (ICNC) values retrieved from combined lidar–radar observations are used for comparison with the simulation results. The simulations show that the observed smoke pollution levels in the upper troposphere were high enough to trigger strong ice nucleation. The simulations also corroborate the hypothesis stated in Part 1 (Ansmann et al., 2025): the persistent smoke layer, continuously observed over the central Arctic during the winter half year 2019–2020, was able to widely suppress homogeneous freezing so that the smoke aerosol most probably controlled cirrus formation and properties. The observations suggest that the INP reservoir was continuously refilled from the lower stratosphere. Furthermore, the simulations confirm that the observed high ice saturation ratios of 1.3–1.5 over the North Pole region at cirrus tops (with top temperatures of −60 to −75 °C) point to inefficient INPs, as expected when wildfire smoke particles (organic particles) serve as INPs. Finally, the simulations revealed that ice nucleation in widespread and frequently occurring shallow updrafts (with low amplitudes) seems to be responsible for the observed low ICNC values of typically 1–50 crystals L−1 in the Arctic cirrus virga.